Diversification in Private Equity Funds: On Knowledge Sharing, Risk Aversion, and Limited Attention - Humphery-Jenner, Mark (Journal of Financial and Quantitative Analysis, 2013)
Abstract This paper examines diversification as a source of value creation and destruction in private equity (PE) funds. Previous literature has focused on the “diversification discount” in corporations. However, in PE funds, diversification might increase returns by ameliorating managerial risk aversion and facilitating knowledge sharing. I examine a sample of 1,505 PE funds and show that industry and geographic diversification can increasePE fund returns. This is likely due to knowledge sharing and learning, not merely risk reduction. Diversification can reduce returns if it spreads staff too thinly across industries or is motivated by risk aversion rather than performance bonuses.